A Clinical, Genomic and Proteomic Approach for the Characterization of Fanconi Anemia in Adolescent and Young Adult (AYA) Patients : A Single Center Study of 55 Patients from a National Bone Marrow Failure Referral Center - Hussain, Taimoor; Alaiya, Ayodele; Dasouki, Majed; Alzahrani, Hazzaa; Al-Sabbagh, Afnan; Al Ammari, Raghad; Ghabashi, Emad; Demirkaya, Abdullah Faruk; Alawwami, Moheeb; Chaudhri, Naeem A.; Alsharif, Fahad Z.; Rasheed, Walid; et al. (My University)
Objective: Bleeding is one of the major complications of surgical procedures. Severe bleeding can be seen after liver injury. Various methods have been described in the literature for stopping liver bleeding such as compression, Pringle maneuver, and other hemostatic agents have been used. In this study, the use of anti-inflammatory, antioxidant, antimicrobial, analgesic, and anticoagulant agents described in the literature were evaluated for hemostatic efficacy following liver injuries. Materials and Methods: In this study 28 Wistar albino female / male rats from out-bred production were used. Animals were divided in 4 groups. After liver damage model creation, various herbal substances were applied to the liver. Hematocrit and platelet counts were measured. In addition, for histopathologic changes in the liver parenchyma, the rats were sacrificed, and the liver was resected. Results: The amount of bleeding (p: 0.001) and the preoperative and postoperative hematocrit changes (p: 0.009) were statistically significant between the groups. There was no significant difference in connective tissue growth (p: 0.065) and necrosis (p: 0.062). There were significant differences in inflammation and without karyorrhexis (p: 0.003). Discussion: Histopathological examinations showed that the groups using active agents had more connective tissue and karyorrhexis. Therefore these tissues could help to stop bleeding.
Keywords: Liver bleeding; Herbal medicine; hemostatic agent